'Zombies ahead!' A study of how hacked digital road signs destabilize the physical space of roadways. (February 2014) - Olofsson, Jennie
This article explores some of the ways in which hacked Changeable Message Signs (CMSs) destabilize the physical space of motor transport spaces and jeopardize the institutionalized function of travel. While CMSs draw attention to the correlation between motorists' current positions, possible inconveniences ahead and their final destination, hacked CMSs and the subsequent projection of unsanctioned messages destabilize this correlation. Hence, the seemingly straightforward relationship between motor transport spaces and the activities of motorists, pedestrians and passers-by is in fact fashioned by the particular kind of message that is displayed at any given moment. Focusing on the spatial effects of hacked CMSs and how the dissemination of unsanctioned information points to the social stratifications of motor transport spaces, hacking is understood as a means of combating the disciplinary regimes of roadways.